2012
DOI: 10.1080/15389588.2011.627957
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Alcohol and Drugs in Oral Fluid From Truck Drivers in Norway

Abstract: The proportion of oral fluid samples containing psychoactive substances was lower for truck drivers than for car or van drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
1
20
0
2
Order By: Relevance
“…In a recent Norwegian study of 882 truck drivers, psychoactive substances were detected in low prevalence in oral fluid samples. Alcohol was found in only 1 case (0.1%), THC was detected in 6 cases (0.7%), amphetamines were found in 2 cases (0.2%), cocaine and benzoylecgonine were found in 7 cases (0.8%), and opiates were found in 2 cases (0.2%; Gjerde et al 2012). Our research group has also published 2 studies in this area.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent Norwegian study of 882 truck drivers, psychoactive substances were detected in low prevalence in oral fluid samples. Alcohol was found in only 1 case (0.1%), THC was detected in 6 cases (0.7%), amphetamines were found in 2 cases (0.2%), cocaine and benzoylecgonine were found in 7 cases (0.8%), and opiates were found in 2 cases (0.2%; Gjerde et al 2012). Our research group has also published 2 studies in this area.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, the study indicates that the incidence of drug use in truck drivers at a terminal port in Brazil is very similar to that reported in other previously published studies (Knauth et al 2002;Nascimento et al 2007;Pechansky et al 2010;Takitane et al 2013); however, use of cannabis was not observed in our study. Gjerde et al (2012) observed in a Norwegian study that the percentage of drivers whose oral fluids tested positive for alcohol or drugs was very low (alcohol: 0.1%; amphetamine: 0.2%; cannabinoids: 0.7%; cocaine: 0.8%). This may be a result of more frequent monitoring of vehicles at checkpoints and severe punishment for driving under the influence of alcohol or drugs in Norway (Gjerde et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Gjerde et al (2012) observed in a Norwegian study that the percentage of drivers whose oral fluids tested positive for alcohol or drugs was very low (alcohol: 0.1%; amphetamine: 0.2%; cannabinoids: 0.7%; cocaine: 0.8%). This may be a result of more frequent monitoring of vehicles at checkpoints and severe punishment for driving under the influence of alcohol or drugs in Norway (Gjerde et al 2012). In addition, drivers are not entitled to refuse random breath testing or evidential breath testing or blood sampling in cases of suspected driving under the influence of alcohol or drugs.…”
Section: Discussionmentioning
confidence: 94%
“…In recent studies in Norway, the refusal rate was 3-6% (8,22,61). In an American study, the refusal rate was 8-11% when giving an incentive of 10 or 20 $ (9).…”
Section: Samplingmentioning
confidence: 99%